Efficacy of Dienogest on Pelvic Pain and Dyspareunia: Comprehensive Meta-Analysis and Systematic Review - Sutrisno Sutrisno; Wildan Aulia Firdaus (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Endometriosis is a severe disorder marked by endometrial tissue outside the uterus and linked to infertility, although typically manifesting as discomfort in the form of dysmenorrhea, dyspareunia, and pelvic pain. Dienogest is indicated as a first-line hormone treatment for endometriosis-related discomfort. The aim of this study is to analyze the efficacy of Dienogest on treating pelvic pain and dyspareunia compared to placebo or combined oral contraceptives (COC) in women with endometriosis. Methods: A systematic search is conducted in PubMed, ScienceDirect, and Google Scholar. The PRISMA 2020 rules were used to screen the articles that were obtained. For the review, studies that examined how using dienogest in improving endometriosis were exposed to were taken into consideration. In a meta-analysis utilizing a random-effects model, odds ratios with their 95% confidence intervals (CI) were provided. Results: Five studies that met the criteria for inclusion were determined to be pertinent to the association between using dienogest in improving endometriosis (n=711). The Dienogest group had substantially improve pelvic pain with a mean difference of 1.01 (95% CI 1.2, 0.82; p<0.00001) and dyspareunia with a mean difference of 0.58 (95% CI 1.09, 0.08; p=0.02) compared to placebo. Compared to combined oral contraceptives, COC had substantially improves dyspareunia with a mean difference of 0.99 (95% CI 0.62, 1.37; p<0.00001) and pelvic pain with a mean difference of 1.15 (95% CI 0.23, 0.83; p=0.01). Conclusion: Dienogest should be considered as an alternate treatment for endometriosis-related symptoms. In double-blind research, DNG efficacy was compared to placebo.